A SYSTEMATIC ANALYSIS OF THE NATURE AND PATTERNS OF SHADOW ECONOMY - Zaveruha M.M. (Pressing Problems of Public Administration, 2015)
The analysis of the formation and functioning of the shadow economy. The need for asystematic approach to the nature and characteristics of the shadow economy.